Comparison of the stability of discontinuous Galerkin and finite-difference methods - Čiegis, Raimondas; Čiegis, Remigijus; Suboč, Olga (Lietuvos matematikos rinkinys, 2002)
In this article we present stability analysis of two discrete schemes, which are used to solve a parabolic problem on adaptive nonstationary meshes. The influence of interpolation and projection errors is investigated. It is proved that interpolation error accumulates during computations while projection error has much better stability properties. Numerical examples illustrate these theoretical results.